RpNGS: an automated platform for pathogen identification and monitoring in clinical metagenomics data - Jing Zhou; Yao Tian; Min Yang; Ting Hao; Jun Ma; Shengyu Wang (PeerJ)
Background The capacity of metagenomic sequencing-based diagnostics to fully identify infections have made them useful instruments in clinical practice. We introduce an interactive platform that runs on a local server-class hardware resource and implements a number of open-source programs. Results RpNGS integrates an interactive tabular interface for the management of experimental processes, patient metadata, and automated sequencing analysis. This technology optimizes clinical reporting by autonomously generating standardized reports in Word format. We have utilized the platform on an artificial microbial community reference panel and several clinical metagenomics datasets from public databases to demonstrate the efficacy of this workflow. Conclusions RpNGS is an innovative, user-friendly standalone application designed to store laboratory data (including reagents, primers, contaminants and run configurations), manage clinical metadata, process FASTQ files and produce analytical and comparative reports (including Word documents) that can be readily reviewed and certified. Its interactive interface necessitates no programming expertise, rendering it an invaluable instrument for clinical metagenomic pathogen identification.